Diverse Roles of Polyethylene Glycol in Organic Transformations: A Review - Poddar, Roona (Current Green Chemistry, 2017)
Background: The biggest challenge for contemporary organic syntheses is to discover new methods for sustainable, clean and green chemistry. In this context, Poly Ethylene Glycol (PEG) has proven its effectiveness as a potential substitute for reaction media, catalyst or promoter. Owing to its biodegradable and non-toxic nature, it is being actively scrutinized as a green solvent for organic transformation. Method: Polyethylene glycols are readily utilized under mild conditions and have high selectivity and reactivity with broad range of substrate acceptance to make it better reaction medium for a wide variety of organic transformations. Furthermore, it has been revealed in a number of reports that polyethylene glycol can be efficiently combined with other catalyst from the field of organocatalysis or metal - catalysis resulting in synergistic effect. Moreover, polyethylene glycol is stable under high temperature, microwave irradiation and can act as both liquid and solid phase catalyst. Conclusion: This study demonstrates as overview on the most recent advances in the current field.
Keywords: solid support